Management of fracture shaft of femur in children with Titanium Elastic Nailing (TEN) at Dhaka Medical College Hospital, Bangladesh (Journal of Dhaka Medical College, 2015)
Context: Management of femoral diaphyseal fractures in children with ages 5 to 15 years is controversial. There has been debate of operative fixation worldwide. Objective: To evaluate the outcome of Titanium Elastic Nail (TEN) for the treatment of fracture of shaft of femur in pediatric age group. Method: Ten children aged 5-15 years with femoral diaphyseal fractures were stabilized with Titanium Elastic Nail (TEN). The results were evaluated using Flynns Scoring Criteria. Two nails were used in each fracture. Radiological union in all cases was achieved in a mean time of 8 weeks. Full weight bearing was possible in a mean time of 06 weeks. Result: The results were excellent in 10 patients (100%). Intramedullary fixation by TEN is an effective treatment of fracture of femur in properly selected patients of the 5-15 years age group. Conclusion: Treatment of femoral shaft fracture in children aged 5-15years by TEN is ideal, as it hastens fracture union, reduce the rate of mal union, shortening and allow early rehabilitation. DOI: http://dx.doi.org/10.3329/jdmc.v23i1.22689 J Dhaka Medical College, Vol. 23, No.1, April, 2014, Page 24-30